Health & Justice - Brinkley-Rubinstein, Lauren; Gideon, Lior.; Guastaferro, Wendy P.; Taxman, Faye.; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: BioMed Central.)
Health & Justice is a fully open access, peer-reviewed journal presenting original experimental research and commentary on the area of health and well-being of people involved in the adult or juvenile justice system, including policy makers and practitioners. The journal fills a gap in the literature by encouraging interdisciplinary, translational science to explore possible ways of introducing health innovations in the justice system. Health & Justice covers a broad array of research topics and is open to submissions from varied disciplines, including: public health, criminology and criminal justice, medical science, psychology, sociology, neuroscience, anthropology and the social sciences. We welcome original research, meta-analyses and systematic reviews, implementation science, study protocols and clinical practice guidelines, as well as commentary and perspectives on new and upcoming issues in the field. Health & Justice aims for a broad reach, including researchers, justice practitioners, such as judges, prosecutors and defenders, probation officers, law-enforcement, treatment providers, plus mental health and medical personnel working with justice-involved individuals. Health & Justice aims to: Present original experimental research on the area of health and well-being of people involved in the adult or juvenile justice system, including people who work in the system; Present meta-analysis or systematic reviews in the area of health and justice for those involved in the justice system; Provide an arena to present new and upcoming scientific issues; Present translational science$1 (Bthe movement of scientific findings into practice including programs, procedures, or strategies; Present implementation science findings to advance the uptake and use of evidence-based practices; and, Present protocols and clinical practice guidelines.s
Keywords: Criminology; Public health; Social policy; Community psychology; Criminology; Public Health; Social Policy; Community Psychology